2016
DOI: 10.5812/ijp.5096
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Probiotics on Reducing Hospitalization Duration in Infants With Hyperbilirubinemia

Abstract: Background: Approximately 60% of term and 80% of premature infants are hospitalized for hyperbilirubinemia in the first week of life. Hyperbilirubinemia is the most common cause of infant hospitalization and readmission. Due to the high frequency of hyperbilirubinemia in infants and the high costs of treatment, it is necessary to find a way to decrease hospitalization duration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
13
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 17 publications
5
13
0
1
Order By: Relevance
“…Similar observations were made by Raguz et al, Torkaman et al and Khurana et al 8,9,21 However Studies done by Lin et al and Lin et al showed no significant difference in the hospital stay between test and control group. 17,18…”
Section: Duration Of Hospital Staysupporting
confidence: 83%
See 1 more Smart Citation
“…Similar observations were made by Raguz et al, Torkaman et al and Khurana et al 8,9,21 However Studies done by Lin et al and Lin et al showed no significant difference in the hospital stay between test and control group. 17,18…”
Section: Duration Of Hospital Staysupporting
confidence: 83%
“…In our study, the mean duration of phototherapy in test and control group was 1.10.3 days and 1.90.9 days respectively which is significant (p=0.01). This view was also echoed by study done by Torkaman et al 9 Demirel et al reported that the administration of probiotics is effective in reducing the duration of phototherapy in very low birth weight (VLBW) newborns of gestational age ≤32 weeks with jaundice. 10 Liu et al reported that therapy with probiotics in term newborns with jaundice lowered the serum bilirubin levels significantly in the treatment group compared to the control group.…”
Section: Duration Of Phototherapymentioning
confidence: 86%
“…In study done at Torkman et al, and Mehmet mutlu et al, all enrolled newborns were born by NVD. 2,3 In group 1, the mean frequency of stools were 3.76±1.08, 3.72±0.95, 4.02±0.92, 4.03±0.98, 4.09±1.04, 4.01±0.93 and 3.85±1.02 on1 st , 2 nd , 3 rd , 4 th , 5 th , 6 th and 7 th day of life respectively. In group B, the mean frequency of stools were 3.31±1.10, 3.39±0.98, 3.45±0.99, 3.72±0.98, 3.77±1.03, 3.88±0.90 and 3.75±1.00 on 1 st , 2 nd , 3 rd , 4 th , 5 th , 6 th and 7 th day of life respectively as shown in table no 2.…”
Section: Resultsmentioning
confidence: 99%
“…This evidence supports the use of probiotics as a therapeutic strategy for the prevention of NEC in newborns. 6,7 Furthermore, probiotics have been widely studied in infants; for example, a recent study suggests that probiotics may be beneficial as an adjunct treatment for term infants with hyperbilirubinemia by reducing the duration of hospitalization, 8 and in the prophylaxis and treatment of urinary tract infections in children. 9 The lower prevalence of protective Lactobacillus or Bifidobacterium species in preterm infants compared to term infants makes these species of probiotics a target for the prevention of NEC.…”
Section: Introductionmentioning
confidence: 99%